2009
DOI: 10.1086/597006
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Yellow Fever Vaccination for 102 HIV‐Infected Patients

Abstract: Compared with HIV-uninfected individuals, HIV-infected patients respond to 17DV with lower reactive NTs, more often demonstrate nonprotective NTs, and may experience a more rapid decline in NTs during follow-up. Vaccination with 17DV appears to be safe in HIV-infected individuals who have high CD4 cell counts, although rate of serious adverse events of up to 3% cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 31 publications
5
64
1
7
Order By: Relevance
“…At one year post-vaccination, significantly fewer HIV-infected patients had protective neutralizing antibodies, and their titers were significantly lower than HIV-uninfected persons. 54 In this study, the median CD4 cell count was 537 cells/mm 3 (range = 11-1,730 cells/mm 3 ), and the viral load was undetectable in 41 of 102 HIVinfected patients.…”
Section: Americanmentioning
confidence: 55%
See 1 more Smart Citation
“…At one year post-vaccination, significantly fewer HIV-infected patients had protective neutralizing antibodies, and their titers were significantly lower than HIV-uninfected persons. 54 In this study, the median CD4 cell count was 537 cells/mm 3 (range = 11-1,730 cells/mm 3 ), and the viral load was undetectable in 41 of 102 HIVinfected patients.…”
Section: Americanmentioning
confidence: 55%
“…During the first decade after vaccination, the rate of non-protective response for HIVpositive recipients was 23%, which was twice that for HIVnegative recipients. 54 Two recent and well-designed studies suggest that viral load inversely correlates with the immune response to YF vaccine: the lower the viral load at the time of vaccination, the stronger the immune response. Veit and others reported that higher levels of neutralizing antibodies during the first year after immunization were associated with undetectable HIV RNA levels at the time of vaccination.…”
Section: Americanmentioning
confidence: 99%
“…25 The rarity of events precludes definitive conclusions, but the YFV 17D vaccine seems to be safe in pregnancy and in HIV positive individuals who are not overly immunodeficient, with >200 cells/mm 3 , and CDC considers that YFV 17D may be administered if CD4 count is 500/mm 3 , or 25% of total lymphocytes for children aged <6 years. [26][27][28] 29 so the recognized risk factor for thimectomy could be part of a spectrum of risk associated with autoimmune diseases. This possibility should be further investigated, and some speculative hypotheses could be explored, such as cross reaction of preformed antibodies of individuals with autoimmunity with vaccine virus, formation of immune complexes, and antibody enhancement.…”
Section: Risk Factorsmentioning
confidence: 99%
“…101 A recent Cochrane review underlines the importance of viral replication control and immune reconstitution for improving the efficacy and safety of the vaccine in this population. 102 In conclusion, vaccination coverage in HIV-infected patients is still inadequate, despite vaccination being an essential element of disease management in preventing infections preventable by immunization.…”
Section: Yellow Fever Vaccinationmentioning
confidence: 99%